Monster Hunter [videorecording (DVD)] - Anderson, Paul, 1965-; Jovovich, Milla; Jaa, Tony, 1976-; T. I., 1980-; Good, Meagan, 1981- (Sony Pictures Home Entertainment, 2021)
There is another world: a world of dangerous and powerful monsters that rule their domain with deadly ferocity. When an unexpected sandstorm transports Captain Artemis and her unit to a new world, the soldiers are shocked to discover that this hostile environment is home to enormous and terrifying monsters immune to their firepower. In their desperate battle for survival, the unit encounters the mysterious Hunter, whose unique skills allow him to stay one-step ahead of the powerful creatures.